Pengembangan Kewirausahaan Mahasiswa Melalui Usaha Taman Makan Sehat Warmindo Tamans Di Era Pandemi Covid-19 - Pranoto, Aji; Puspita, Ayu Asmi; Saraswaty P.B, Chantica; Pangestu, Tegar Rezki; Wardani, Eka Kusuma; Dwiadi, Qurnia Amanah (DHARMA BAKTI, 2022)
The entrepreneurial learning process must also be able to build entrepreneurial character in students, including the courage to take risks, be able to see the future and create opportunities, be able to modify products by providing added value for consumers, thus creating a difference with competitors (Arasy Alimudin, 2013). Tamtams Warmindo is a food stall developed by several students of IST Akprind Yogyakarta with a menu that focuses on healthy food. The reason the food menu focuses on a healthy food menu is due to the covid-19 pandemic which has created an intention to make healthy eating in the form of simple stalls that are very popular with the public, especially the DIY area. After this business was opened and running for some time, and saw some aspects of the business so that it could qualify for the 2021 Indonesian Student Business Competition (KBMI) program funding.